Toward a sustainable and enhanced iron ore recovery: Biobeneficiation review - Francis Gitau; Oladunni Oyelola Alabi; Fatai Olufemi Aramide; Talabi Henry Kayode; Mary Nelima Ondiaka (Society for Mining, Metallurgy & Exploration, 2024)
Iron ore is essential in steelmaking but high-grade ores have diminished, making it necessary to turn to low-grade ores, which need further beneficiation to upgrade the iron content. Biobeneficiation techniques such as bioleaching, bioflotation and bioflocculation have proven successful in iron ore processing. Consequently, these methods have emerged as sustainable alternatives to conventional beneficiation. The biobeneficiation processes occur in mild conditions using bioreagents and biosurfactants derived from microbes, and offer a reduction of chemicals used in processing. This potentially offers methods that are relatively energy efficient, cost effective and environmentally friendly while tackling the constraints of dwindling high-grade iron ore resources.